Oxygen evolution reaction electrocatalyst and preparation method and application thereof

Through electrodeposition, heat treatment and vulcanization, an oxygen evolution reaction electrocatalyst with a two-dimensional structure and rich oxygen vacancy was prepared, which solved the problem of high cost of precious metal catalysts, achieved low-cost, high-performance and stable electrocatalysts, and significantly improved the charge transfer performance and stability of the oxygen evolution reaction.

CN119640310APending Publication Date: 2025-03-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311199454.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, precious metal catalysts are costly and it is difficult to develop low-cost, high-performance and stable oxygen evolution reaction electrocatalysts, especially in spinel structure transition metal oxides have insufficient electrocatalytic activity at high current density.

Method used

By electrodeposition of metal salt solution or metal molten salt on the surface of the metal substrate, followed by heat treatment and vulcanization, an oxygen evolution reaction electrocatalyst with a two-dimensional structure, a large specific surface area and a large number of active sites was prepared. This method enhances charge transfer performance by introducing oxygen vacancies and heterostructures.

Benefits of technology

The prepared oxygen evolution reaction electrocatalyst exhibits a low overpotential under the same current density, and has good stability under high current density and voltage conditions, and can operate stably for more than 100 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640310A_ABST
    Figure CN119640310A_ABST
Patent Text Reader

Abstract

The invention relates to the field of oxygen evolution reaction electrocatalysts, and discloses an oxygen evolution reaction electrocatalyst and a preparation method and application thereof. The invention discloses a method for preparing an oxygen evolution reaction electrocatalyst. The method comprises the following steps: (1) carrying out electrodeposition on a metal salt solution or metal molten salt on the surface of a metal substrate; (2) carrying out heat treatment on the electro-deposition product in the step (1); (3) mixing a heat treatment product obtained in the step (2) with a sulfur-containing compound for vulcanization; wherein the heat treatment condition comprises the steps that the temperature is increased to 300 DEG C or above at the speed of 1-5 DEG C / min, and the temperature is maintained for 1-5 h. The self-supporting oxygen evolution reaction electrocatalyst is synthesized, rich oxygen vacancies and heterostructures are successfully introduced through the vulcanization process, charge transfer of the oxygen evolution reaction is jointly enhanced, lower overpotential is shown under the same current density, stable operation can be achieved, and time is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of oxygen evolution reaction electrocatalysts, and in particular to oxygen evolution reaction electrocatalysts and preparation methods and applications thereof. Background Art

[0002] As a green hydrogen technology, the use of renewable energy to electrolyze water to produce hydrogen has attracted widespread attention worldwide. Compared with traditional alkaline solution electrolyzer technology and proton exchange membrane water electrolysis, alkaline membrane water electrolysis technology has the dual advantages of low cost and high membrane electrode efficiency because it can use non-precious metal catalysts. Among them, the development of highly active and stable non-precious metal electrocatalysts for oxygen evolution reaction (OER) is the key to anion exchange membrane electrolyzer (AEMWE). Traditional precious metal catalysts (such as Pt / C, IrO2 and RuO2) have good catalytic activity, but their high cost limits their development. Therefore, there is an urgent need to develop low-cost, high-performance and stable hydrogen evolution reaction (HER) and OER catalysts.

[0003] Transition metal oxides with spinel structure (AB2O4) have high electrocatalytic activity, good charge transfer and stability under alkaline conditions, and are considered to be ideal choices for AEMWE anode materials. However, under high current density, the electrocatalytic activity of spinel structure in AEMWE still needs to be further improved. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems existing in the prior art and to provide an oxygen evolution reaction electrocatalyst and a preparation method and application thereof.

[0005] In order to achieve the above object, the first aspect of the present invention provides a method for preparing an oxygen evolution reaction electrocatalyst, the method comprising:

[0006] (1) Electrodepositing a metal salt solution or a metal molten salt on the surface of a metal substrate;

[0007] (2) heat treating the electrodeposited product of step (1);

[0008] (3) mixing the heat-treated product of step (2) with a sulfur-containing compound for sulfurization;

[0009] The heat treatment conditions include: heating to 300°C or above at a rate of 1-5°C / min, and maintaining the temperature for 1-5h.

[0010] The second aspect of the present invention provides an oxygen evolution reaction electrocatalyst prepared by the above method. The prepared product exhibits a two-dimensional structural morphology, has a large specific surface area and a large number of active sites; the prepared electrode material is a heterogeneous structure; the prepared product has a large number of oxygen vacancies; the heterogeneous structure and oxygen vacancies can enhance the charge transfer performance and reduce the charge transfer resistance.

[0011] The third aspect of the present invention provides the use of the above oxygen evolution reaction electrocatalyst in oxygen evolution by electrolysis of water, wherein the oxygen evolution electrode exhibits good stability.

[0012] Through the above technical scheme, the present invention synthesizes a self-supporting oxygen evolution reaction electrocatalyst, successfully introduces abundant oxygen vacancies and heterogeneous structures through the sulfurization process, and jointly enhances the charge transfer of the oxygen evolution reaction. The material has a two-dimensional structure, a large specific surface area and active sites. The oxygen evolution reaction electrocatalyst anode of the present invention exhibits a lower overpotential at the same current density, and the AEMWE using the oxygen evolution reaction electrocatalyst anode of the present invention exhibits good stability under conditions of higher current density and voltage, and can stably and continuously operate for more than 100 hours at a higher current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a SEM image of the CoCuOx / NF catalytic electrode prepared in Example 1;

[0014] Figure 2 is a SEM image of the S-CoCuOx / NF catalytic electrode prepared in Example 1;

[0015] Figure 3 It is the LSV scanning diagram of Example 1, Example 10, Comparative Example 1, Comparative Example 2 and the carrier NF anode;

[0016] Figure 4 Polarization curves of the electrolysis system using Example 1 and Comparative Example 1 as anodes;

[0017] Figure 5 The electrolysis system with Example 1 and Comparative Example 1 as anode is at 1A / cm 2 Stability test results under current density;

[0018] Figure 6 is the X-ray photoelectron spectrum of the S-CoCuOx / NF electrode of Example 1;

[0019] Figure 7 are AC impedance spectra of Example 1, Example 10, Comparative Example 1, Comparative Example 2 and carrier NF;

[0020] Figure 8 This is the X-ray diffraction pattern of the S-CoCuOx / NF electrode in Example 1. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] A first aspect of the present invention provides a method for preparing an oxygen evolution reaction electrocatalyst, the method comprising:

[0023] (1) Electrodepositing a metal salt solution or a metal molten salt on the surface of a metal substrate;

[0024] (2) heat treating the electrodeposited product of step (1);

[0025] (3) mixing the heat-treated product of step (2) with a sulfur-containing compound for sulfurization;

[0026] Wherein, the heat treatment conditions include: heating to 300°C and above (can be 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, The temperature may be 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C or any two of the above values, and the values ​​within the range, preferably 300-500°C, more preferably 300-400°C), and maintained at this temperature for 1-5h, which may be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4.5h, 5h or any two of the above values, and the values ​​within the range, preferably 2-4h.

[0027] Preferably, the molar ratio of the metal element to the sulfur-containing compound in the metal salt solution or metal molten salt is 1:0.1-1, and can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or a range formed by any two of the above values ​​and a value within the range.

[0028] In the present invention, in order to make the spinel structure formed by the product after heating obtain rich oxygen vacancies and heterogeneous structure and enhance the charge transfer of the oxygen evolution reaction, the sulfurization conditions include: the temperature is 100-200°C, which can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or the range formed by any two of the above values ​​and the values ​​within the range; the time is 3-9h, which can be 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h or the range formed by any two of the above values ​​and the values ​​within the range.

[0029] Preferably, the concentration of the metal in the metal salt solution is 0.5-3mmol / mL, which can be 0.5mmol / mL, 0.6mmol / mL, 0.7mmol / mL, 0.8mmol / mL, 0.9mmol / mL, 1mmol / mL, 1.1mmol / mL, 1.2mmol / mL, 1.3mmol / mL, 1.4mmol / mL, 1.5mmol / mL, 1.6mmol / mL, 1.7mmol / mL, 1.8mmol / mL, 1.9mmol / mL, 2mmol / mL, 2.1mmol / mL, 2.2mmol / mL, 2.3mmol / mL, 2.4mmol / mL, 2.5mmol / mL, 2.6mmol / mL, 2.7mmol / mL, 2.8mmol / mL, 2.9mmol / mL, 3mmol / mL or the range formed by any two of the above values, and the value within the range.

[0030] In the present invention, in order to obtain an oxygen evolution reaction electrocatalyst with a spinel structure, the metal element in the metal salt solution or metal molten salt includes at least one of Co, Cu and Mn; preferably, the metal element in the metal salt solution or metal molten salt includes Co and Cu; more preferably, the amount ratio of Co and Cu is 1:0.1-1, which can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or the range formed by any two of the above values ​​and the value within the range. Correspondingly, the metal salt is at least one of a cobalt salt, a copper salt and a manganese salt, preferably at least one of cobalt nitrate, copper nitrate and manganese nitrate. Similarly, the metal molten salt is a molten salt formed by the above metal salts.

[0031] In the present invention, in order to make the spinel structure formed by the product after heating obtain rich oxygen vacancies and heterogeneous structure, and enhance the charge transfer of the oxygen evolution reaction, in step (3), in step (3), the sulfur-containing compound is used in the form of a sulfur-containing compound solution. Preferably, the concentration of the sulfur-containing compound in the sulfur-containing compound solution is 0.1-2 mmol / mL, which can be 0.1 mmol / mL, 0.2 mmol / mL, 0.3 mmol / mL, 0.4 mmol / mL, 0.5 mmol / mL, 0.6 mmol / mL, 0.7 mmol / mL, 0.8 mmol / mL, 0.9 mmol / mL, 1 mmol / mL, 1.1 mmol / mL, 1.2 mmol / mL, 1.3 mmol / mL, 1.4 mmol / mL, 1.5 mmol / mL, 1.6 mmol / mL, 1.7 mmol / mL, 1.8 mmol / mL, 1.9 mmol / mL, 2 mmol / mL or the range formed by any two of the above values ​​and the value within the range.

[0032] In the present invention, the sulfur-containing compound is not limited, and can provide sulfur element. Preferably, the sulfur-containing compound includes at least one of thiourea, sodium sulfide, sodium dodecyl sulfate, carbon disulfide and sodium thiosulfate.

[0033] In the present invention, there is no special requirement for the method of electrodeposition, as long as the metal in the metal salt solution or the metal molten salt can be deposited on the metal substrate. In order to obtain a spinel structure oxygen evolution reaction electrocatalyst, the method of electrodeposition includes: placing the metal substrate as a working electrode in the metal salt solution or the metal molten salt for electrodeposition; preferably, relative to the reference electrode, the voltage of the electrodeposition is -1.5V to -0.5V, which can be -1.5V, -1.4V, -1.3V, -1.2V, -1.1V, -1V, -0.9V, -0.8V, -0.7V, -0.6V, -0.5V or the range formed by any two of the above values ​​and the value within the range, and the reference electrode is preferably a saturated calomel electrode.

[0034] Preferably, the electrodeposition increases the thickness of the metal substrate by 5-20 μm, which may be 5 μm, 7 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm or a range formed by any two of the above values ​​and a value within the range.

[0035] More preferably, the electrodeposition conditions include: a temperature of 20-30°C, which may be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C or any two of the above values ​​in the range and the value within the range, and a time of 5-15min, which may be 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min or any two of the above values ​​in the range and the value within the range. More preferably, the metal substrate includes at least one of foamed iron, foamed titanium, foamed nickel, foamed cobalt and carbon cloth.

[0036] In the present invention, in order to remove impurities on the electrodeposited surface, the method further comprises: the electrodeposited product of step (1) is subjected to a first rinse and / or a first drying before the heat treatment of step (2). Preferably, the first rinse and / or first drying temperature is 60-70°C.

[0037] In the present invention, in order to remove impurities on the surface of the mixed product, the method further comprises: performing a second rinse and / or a second drying on the sulfided product. Preferably, the temperature of the second rinse and / or the second drying is 20-40°C.

[0038] The second aspect of the present invention provides an oxygen evolution reaction electrocatalyst prepared by the above method.

[0039] The third aspect of the present invention provides the use of the above oxygen evolution reaction electrocatalyst in oxygen evolution by electrolysis of water.

[0040] Preferably, the oxygen evolution reaction electrocatalyst is an anode electrocatalyst; more preferably, the electrolysis is carried out under alkaline conditions.

[0041] In the present invention, in actual use, the oxygen evolution reaction electrocatalyst can be directly used as an anode, and the conditions for electrolyzing water are: a hydroxide ion concentration of 0.5-1.5M and a temperature of 50-65° C. The cathode can use a Pt / C catalyst sprayed on carbon paper.

[0042] Preferably, the electrolysis is carried out in an anion exchange membrane electrolyzer at a current density of 0.5-1.5 A / cm 2 , more preferably 1-1.5A / cm 2 .

[0043] Example 1

[0044] (1) Preparation of CoCuOx / NF

[0045] The commercial nickel foam (NF, 2×2.5cm 2) was treated in a 5M HCL aqueous solution for 30 minutes to remove the surface oxide layer, treated with ultrapure water (milliq Advantage A10) for 15 minutes, and treated with ultrasonic ethanol (Tianjin Yuanli Technology Co., Ltd.) for 15 minutes, and then dried in vacuum at 60°C. 50mmol of cobalt nitrate hexahydrate (Shanghai Aladdin Biochemical Technology Co., Ltd.) and 20mmol of copper nitrate hydrate (Shanghai Aladdin Biochemical Technology Co., Ltd.) were dispersed in 50mL of ultrapure water by continuous magnetic stirring for 10 minutes, and then a saturated calomel electrode (SCE) was used as the reference electrode, a Pt mesh was used as the counter electrode, and the aforementioned nickel foam was used as the working electrode. The electrode was reacted at a constant potential of -1V (relative to SCE) at 25°C for 10 minutes for electrodeposition to obtain a pink aqueous solution. After the electrodeposition is completed, the electrode is rinsed with ultrapure water, dried in vacuum at 60°C, and heated to 350°C in a muffle furnace at a rate of 3°C / min and maintained for 3h. The resulting electrode is named CoCuOx / NF. The scanning electron microscope photo is shown in Figure 1 As shown, the thickness increases by 15 μm.

[0046] (2) Preparation of S-CoCuOx / NF

[0047] The synthesized CoCuOx / NF was hydrothermally treated with thiourea (TU, Shanghai Aladdin Biochemical Technology Co., Ltd.) to prepare S-CoCuOx / NF. The specific steps were as follows: 40 mmol TU was dispersed in 40 mL ultrapure water, stirred continuously by magnetic stirring for 5 minutes, and then the solution was transferred to a 50 mL teflon-lined stainless steel autoclave containing the synthesized CoCuOx / NF plate. The sulfurization process was carried out at 150 ° C for 6 hours, and then the autoclave was cooled to room temperature. S-CoCuOx / NF was washed with ethanol and ultrapure water and then dried. Scanning electron microscope photos are shown in Figure 2 As shown, it can be seen that there is a thin film on the surface of S-CoCuOx / NF, showing a two-dimensional structural morphology, with a large specific surface area and a large number of active sites.

[0048] Example 2

[0049] The method of Example 1 was followed, except that a voltage of -0.15 V was used in the preparation of CoCuOx / NF.

[0050] Example 3

[0051] The method of Example 1 was followed, except that a voltage of -0.5 V was used in the preparation of CoCuOx / NF.

[0052] Example 4

[0053] The method of Example 1 was followed, except that the electrodeposition time in the preparation of CoCuOx / NF was changed to 20 min.

[0054] Example 5

[0055] The method of Example 1 was followed, except that the electrodeposition time in the preparation of CoCuOx / NF was changed to 5 min.

[0056] Example 6

[0057] The method of Example 1 is followed, except that in the preparation of CoCuOx / NF, after the electrodeposition is completed, the heating temperature is 250°C.

[0058] Example 7

[0059] The method of Example 1 was followed, except that during the preparation of S-CoCuOx / NF, 20 mmol TU was dispersed in 40 mL ultrapure water.

[0060] Example 8

[0061] The method of Example 1 was followed, except that during the preparation of S-CoCuOx / NF, 60 mmol TU was dispersed in 40 mL ultrapure water.

[0062] Example 9

[0063] The method of Example 1 was followed, except that during the preparation of S-CoCuOx / NF, the sulfurization process was carried out at 120°C.

[0064] Example 10

[0065] The method of Example 1 was followed, except that copper nitrate was not added. The resulting electrode was named S-CoOx / NF.

[0066] Comparative Example 1

[0067] 10 mg of IrO2 powder (Johnson Matthey) was ultrasonically dispersed in 1 mL of solution (the solution composition was: anionic polymer (0.5 mg, PiperION), 800 μL of isopropanol (Shanghai Aladdin Biochemical Technology Co., Ltd.) and 200 μL of ultrapure water) to prepare a spraying solution, and then the ink solution was sprayed on the nickel foam. The IrO2 loading was about 1.2 mg / cm 2 The obtained electrode is named IrO2 / NF.

[0068] Comparative Example 2

[0069] The method of Example 1 is followed, except that copper nitrate is not added and step (2) is not performed. The resulting electrode is named CoOx / NF.

[0070] Test Case

[0071] (1) The OER performance of the above-mentioned different anode catalysts was tested using a three-electrode system and a Shanghai Chenhua 760E electrochemical workstation.

[0072] Before the test, N2 was passed through the electrolyte (1M KOH solution) for about 30 minutes to saturate the electrolyte with N2, so that the oxygen content in the electrolyte was infinitely close to 0. Then the three-electrode test system was assembled so that the voltage test range was set at (0-1.20V (vs.RHE)), and the CV test was performed at a scan rate of 20mV / s, with the number of cycles set to 20 to fully activate the sample and fully expose the active sites; then O2 was passed through the electrolyte for 30 minutes to saturate the electrolyte with O2, and an LSV test was performed with a scan rate of 10mV / s, and the OER test scan range was 1.2-1.80V (vs.RHE). The test results are as follows: Figure 3 As shown, Figure 3 The overpotential is obtained by subtracting 1.23 V from the voltage value in the figure. S-CoCuOx / NF (Example 1) at 100 mA / cm 2 Under the current density, the oxygen evolution overpotential is 313mV, which is significantly better than the carrier NF, IrO2 / NF (Comparative Example 1, oxygen evolution overpotential is 450mV), CoOx / NF (Comparative Example 2, oxygen evolution overpotential is 410mV), S-CoOx / NF (Example 10, oxygen evolution overpotential is 350mV) and CoCuOx / NF (Example 1, oxygen evolution overpotential is 370mV). In addition, the electrode of Example 2 is 100mA / cm 2 At the current density of 100 mA / cm, the oxygen evolution overpotential is 323 mV. 2 At the current density of 100 mA / cm, the oxygen evolution overpotential is 328 mV. 2 At the current density of 100 mA / cm, the oxygen evolution overpotential is 335 mV. 2 At the current density of 100 mA / cm, the oxygen evolution overpotential is 330 mV. 2 At the current density of 100 mA / cm, the oxygen evolution overpotential is 330 mV. 2 At the current density of 100 mA / cm, the oxygen evolution overpotential is 340 mV. 2 At the current density of 100 mA / cm, the oxygen evolution overpotential is 343 mV. 2 At this current density, the oxygen evolution overpotential is 348 mV.

[0073] (2) The effective area of ​​the single cell is 4 square centimeters, and it is composed of an anode (electrodes prepared in Example 1 and Comparative Example 1), a cathode, an anion exchange membrane (AEM, PiperION, 40 μm) and two stainless steel current collectors. The anode is S-CoCuOx / NF and IrO2 (4 cm 2 ), the cathode was sprayed with 20 wt% Pt / C commercial catalyst (Johnson Matthey) on Toray carbon paper 060 (150 μm thick, 4 cm 2 Size), Pt loading is 0.4 mg / cm 2 The AEM was placed between the positive and negative electrodes, immersed in a 1.0M KOH solution at 60°C for 12 hours, and rinsed with ultrapure water. The AEMWE was tested at 60°C with 1M KOH and a flow rate of 8mLmin. The performance of the AEMWE was evaluated by LSV at 1.2-2.2V and time potentiometry. Figure 4 As shown in the figure, the performance of the Pt / C / / S-CoCuOx / NF AEM electrolysis system is better than that of the Pt / C / / IrO2 electrolysis system. 2 The durability was evaluated under the condition of Figure 5 As shown, the stability of the Pt / C / / S-CoCuOx / NF AEM electrolysis system is also significantly better than that of the Pt / C / / IrO2 electrolysis system.

[0074] (3) The prepared S-CoCuOx / NF electrode (Example 1) has a large number of oxygen vacancies (measured by XPS, such as Figure 6 As shown), the charge transfer efficiency is enhanced, as Figure 7 (Example 1, Example 1, Example 10, Comparative Example 1, Comparative Example 2 and carrier NF) As shown in the AC impedance spectrum, S-CoCuOx / NF (Example 1) has the smallest charge transfer resistance.

[0075] (4) The prepared S-CoCuOx / NF electrode (Example 1) was measured by XRD to have a heterogeneous structure (such as Figure 8 As shown), S-CoCuOx / NF contains Ni3S2, Co9S8, and Cu 31 S 16 .

[0076] From the above results, it can be seen that the embodiment of the present invention introduces abundant oxygen vacancies and heterogeneous structures, which jointly enhance the electron and charge transfer of the oxygen evolution reaction, show a lower overpotential at the same current density, and the AEMWE of the anode is 1A / cm 2The electrode prepared by the present invention has abundant oxygen vacancies and small charge transfer resistance, which enhances the charge transfer of the oxygen evolution reaction.

[0077] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing an oxygen evolution reaction electrocatalyst, characterized in that: The method comprises: (1) Electrodepositing a metal salt solution or a metal molten salt on the surface of a metal substrate; (2) heat treating the electrodeposited product of step (1); (3) mixing the heat-treated product of step (2) with a sulfur-containing compound for sulfurization; The heat treatment conditions include: heating to 300°C or above at a rate of 1-5°C / min, and maintaining the temperature for 1-5h.

2. The method according to claim 1, wherein: During the heat treatment, the temperature is raised to 300-500°C, preferably 300-400°C; And / or, the maintenance time is 2-4h; And / or, the heating rate is 2-4°C / min; And / or, the molar ratio of the metal element in the metal salt solution or the metal molten salt to the sulfur-containing compound is 1:0.1-1; And / or, the vulcanization conditions include: temperature of 100-200° C. and time of 3-9 hours.

3. The method according to claim 1 or 2, wherein the concentration of the metal in the metal salt solution is 0.5-3 mmol / mL; And / or, the metal element in the metal salt solution or the metal molten salt includes at least one of Co, Cu and Mn; Preferably, the metal elements in the metal salt solution or metal molten salt include Co and Cu; Preferably, the molar ratio of Co to Cu is 1:0.1-1.

4. The method according to claim 1 or 2, wherein: In step (3), the sulfur-containing compound is used in the form of a sulfur-containing compound solution; Preferably, the concentration of the sulfur-containing compound in the sulfur-containing compound solution is 0.1-2 mmol / mL; Preferably, the sulfur-containing compound includes at least one of thiourea, sodium sulfide, sodium dodecyl sulfate, carbon disulfide and sodium thiosulfate.

5. The method according to claim 1 or 2, wherein: The electrodeposition method comprises: placing a metal substrate as a working electrode in the metal salt solution or metal molten salt for electrodeposition; Preferably, the voltage of the electrodeposition is -1.5V to -0.5V relative to the reference electrode; Preferably, the electrodeposition increases the thickness of the metal substrate by 5-20 μm.

6. The method according to claim 5, wherein: The conditions of the electrodeposition include: a temperature of 20-30°C and a time of 5-15 minutes; And / or, the metal substrate includes at least one of foamed iron, foamed titanium, foamed nickel, foamed cobalt, foamed nickel-iron, metal felt and carbon cloth.

7. The method according to claim 1 or 2, wherein: The method further comprises: the electrodeposited product of step (1) is subjected to a first rinsing and / or a first drying before the heat treatment of step (2), preferably, the first rinsing and / or the first drying temperature is 60-70° C.; And / or, the method further comprises: performing a second flushing and / or a second drying on the sulfidation product. Preferably, the temperature of the second flushing and / or the second drying is 20-40°C.

8. An oxygen evolution reaction electrocatalyst prepared by the method of any one of claims 1 to 7.

9. Use of the oxygen evolution reaction electrocatalyst according to claim 8 in oxygen evolution by water electrolysis.

10. The use according to claim 9, wherein: The oxygen evolution reaction electrocatalyst is an anode electrocatalyst; Preferably, the electrolysis is carried out under alkaline conditions.